A Geospatial Approach to Potential Rooftop Harvesting of Rain Water in Pirwadi Village, Kolhapur District, Maharashtra (India) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Despite the fact that water covers 71% of  the land surface, water is a limited natural resource. Fresh  water makes up approximately 2.5 percent of total water  on the planet, and it is used for a variety of reasons  including household, irrigation, and industrial. Due to  haphazard population expansion, frequent droughts, and  changing climate patterns, water shortage has become a  major worldwide issue. In a developing country like  India, which has a long history of rural culture, the need  for household water is fast increasing. The practicality of  roof rain water collection in a Pirwadi hamlet in Kolhapur  district (MS), India, was investigated using geospatial  tools. Using a Google picture of the research location,  global mapper, and Arc Gis ver. nine  point three software, the various types of roof areas of  dwellings and buildings in the hamlet were discovered  and computed. The Gould and Nissen formula and  Rande's coefficient of runoff index for various types of  roofs were used to determine the potential of roof rain  water collecting (1999). The whole potential of roof rain  water collection, according to the research, is estimated to  be 11457490.78 Lt., which is more than enough to cover  the village's full annual drinking and cooking demands. In  rural areas, rainwater collection systems are particularly  helpful in alleviating the problem of water scarcity.
Keywords: Geospatial Techniques; Roof Rainwater Harvesting; Runoff Coefficient; Water Scarcity